2017
DOI: 10.18178/ijiet.2017.7.7.927
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Motivation in Language Learning

Abstract: Motivation is one of the fundamental factors in learning a language, the feelings and excitement offered by extra enthusiasm for students to learn a second language in a better way. This study investigated the factors which contribute to motivation in learning English among 80 students of Sekolah Menengah Kebangsaan Lepar Utara. The instrument of the study was a questionnaire adapted from Mohamed Amin, Juriah and Mohd Isa (2001). Findings showed that teachers influence, personal attitude and parental influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 8 publications
3
25
0
Order By: Relevance
“…So teenage students of CPFS course are very self-motivated (m=3.98). The same result was found in the research conducted among the English language learners in Malaysia by Abdul Rahman et al (2017), where it was found that after teachers, students are their own motivators. Moreover, it was observed that 39% of students have been learning English for more than three years, while 13% students started learning the language less than a year ago.…”
Section: Discussionsupporting
confidence: 81%
“…So teenage students of CPFS course are very self-motivated (m=3.98). The same result was found in the research conducted among the English language learners in Malaysia by Abdul Rahman et al (2017), where it was found that after teachers, students are their own motivators. Moreover, it was observed that 39% of students have been learning English for more than three years, while 13% students started learning the language less than a year ago.…”
Section: Discussionsupporting
confidence: 81%
“…The confidence to be persistent in the learning process tended to deteriorate when there were challenges either from teachers or from the 'boring' teaching methods. Hence, the literature has noted that teachers play a great role in managing or increasing students' interest in learning (Fowler and Şaraplı, 2010;Rahman et al, 2017), so it is essential that teachers become good models and prepare exciting teaching methods to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Gorsuch (2011) pointed out that to improve students' speaking skills is by increasing meaningful language input by providing English-rich environments. Another study conducted by Rahman et al (2017) indicated that factors such as teachers, parents, and students' personal attitudes were confirmed in affecting students' motivation in language learning. Similarly, Ekiz and Kulmetov (2016) found that reinforcing the students' beliefs also motivated them to be in the form of aims in learning and future opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the study of Redono (2015) points out that teacher skills, interests, and habits influence student learning. To confirm this concept, Rahman et al (2017) stated the influence of teachers on learning motivation (RAHMAN et al, 2017). And students' learning motivation is significantly related to teacherstudent interaction .…”
Section: Lecturer Behaviourmentioning
confidence: 98%